International Migration and Academic Career: Comparative Analysis of Two Groups of Academic Immigrants in Mexico and Spain - Mendoza Pérez, Cristóbal (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2022)
The article explores reason for migration among two groups of academics (Spaniards and Italians in Mexico and Latin Americans in Spain). While southern Europeans migrate to Mexico because of few quality jobs in academia in their home countries, Latin Americans mostly move to Spain to expand studies. Secondly, the article analyses the labour trajectories of these two groups. Academics from southern Europe have a positive job progression in Mexico, but Latin Americans in Spain mainly achieve precarious job positions with teaching-oriented profiles, so that some choose to leave academia or even consider a new migration. As a bottom line, there is the discussion about whether the studied groups respond to a “knowledge migration” or are “qualified migrants” that migrate due to poor employment prospects.